Developing Intergenerational Relationships - Lynda Spence; Heidi Liss Radunovich (EDIS)
FCS-2282, a 6-page fact sheet by Lynda Spence and Heidi Liss Radunovich, speaks to the importance of children developing intergenerational relationships with older adults. Such relationships can have great benefits for both groups. Includes suggestions for activities for children and elders to do together and an extensive reading list. Published by the UF Department of Family, Youth and Community Sciences, November 2007.